Effect of microwave frequency on dielectric properties of oil palm shell (OPS) and OPS char synthesized by microwave pyrolysis of OPS - Tripathi, M.; Sahu, J.N.; Ganesan, P.; Monash, P.; Dey, T.K. (Elsevier, 2015)
Microwave heating is considered to be a potential, efficient and fast method for thermal treatment of biomass. Therefore, elemental understanding of dielectric properties of biomass is necessary before irradiating it with microwave radiations. Dielectric properties along with penetration depth, relaxation time and static permittivity of oil palm shell COPS) and OPS char were investigated in the frequency ranging between 0.5 and 20 GHz at room temperature. At low frequencies, dielectric constant of UPS was higher than that of UPS char while at higher frequencies, vice versa is observed. Penetration depth for UPS char was higher than that of UPS at low frequencies. Significant variation in relaxation time was observed for OPS in different frequency range, suggesting that the OPS do not obey the Debye equation for dielectrics. Relaxation time and static permittivity for UPS was higher as compared to OPS char. (C) 2015 Elsevier B.V. All rights reserved.